2017
DOI: 10.1155/2017/5407012
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of In Vitro Melanoma Skin Cancer to Photoactivated Hypericin versus Aluminium(III) Phthalocyanine Chloride Tetrasulphonate

Abstract: The sensitivity of human melanoma cells to photoactivated Hypericin (Hyp) compared to aluminium(III) phthalocyanine chloride tetrasulphonate (AlPcS4Cl) is reported in this study. Melanoma cells (A375 cell line) were treated with various concentrations of Hyp or AlPcS4Cl alone, for 1, 4, and 24 hrs; varying doses of laser irradiation alone (594 or 682 nm); or optimal concentrations of PSs combined with laser irradiation. Changes in cell morphology, viability, membrane integrity, and proliferation after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The application of AlPcS 4 Cl in PDT has been widely investigated on several cancers owing to its unique photochemical features ( 3 , 20 , 21 , 23 ). The current study revealed that AlPcS 4 Cl-mediated PDT induced DNA damage response and intrinsic apoptosis pathway as observed by the localization of the PS in the mitochondria/nucleus, upregulation of ATM a DNA damage sensor, high ROS production, reduction in ATP level, decrease in ΔΨM, increase in apoptotic cells, and increment in cytochrome c and caspase 3/7 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of AlPcS 4 Cl in PDT has been widely investigated on several cancers owing to its unique photochemical features ( 3 , 20 , 21 , 23 ). The current study revealed that AlPcS 4 Cl-mediated PDT induced DNA damage response and intrinsic apoptosis pathway as observed by the localization of the PS in the mitochondria/nucleus, upregulation of ATM a DNA damage sensor, high ROS production, reduction in ATP level, decrease in ΔΨM, increase in apoptotic cells, and increment in cytochrome c and caspase 3/7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to its high absorption wavelength in the therapeutic window and its excellent induction of reactive oxygen species (ROS), which is crucial in promoting cell damage. Aluminium-phthalocyanine chloride tetra sulfonate (AlPcS 4 Cl), a sub-class of phthalocyanine, has been extensively employed for PDT application on several tumor types, including oesophageal cancer ( 3 , 20 23 ). It has been established that the subcellular localization of any PSs decides the effectiveness of PDT and, consequently, the cell death pathway ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bax can promote apoptosis in a dimeric form with its homologous proteins. Hyp can increase the Bax/Bcl‐2 ratio in MCF‐7, MDA‐MB‐231, HCT116, SW620, AGC, K562, A375, and Huh7 cells (Arani et al, 2021; Ferenc et al, 2010; Hu et al, 2021; Mirmalek et al, 2015; Naderi et al, 2020; Ndhundhuma & Abrahamse, 2017; Olya et al, 2020). Cyt‐C, which is released by mitochondria, enables the regulation of apoptosis via transduction and amplification of apoptotic signals.…”
Section: Pharmacological Effects Of Hypericinmentioning
confidence: 99%
“…During PDT, hypericin mainly exercises its cytotoxic effect through the production of singlet oxygens ( 1 O 2 ) [ 94 , 95 ], superoxide anion along with other ROS. Moreover, the production of ROS by hypericin has been shown to induce cell death through mechanisms such as apoptosis, necrosis, and autophagy [ 78 , 89 , 96 , 97 , 98 , 99 ]. This has been reported to be associated with hypericin-specific subcellular localization within the cells after PDT treatment [ 70 , 71 , 78 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, novel therapeutic strategies were developed to specifically treat patients with recalcitrant metastases. Cancer immunotherapy in the form of adoptive cell therapy (ACT) has shown the capacity to represent such a therapy, with the ability to harness the patient’s own immunity against tumors [ 99 , 100 , 101 ]. In order to achieve maximum therapeutic efficacy, cancer immunotherapy relies on antigen recognition of tumor cells by cells of the innate immune system such as DCs (antigen-presenting cells (APCs)), which subsequently migrate to secondary lymphoid tissue to prime CTLs that are able to destroy tumors in an antigen-dependent manner [ 49 , 54 ].…”
Section: Introductionmentioning
confidence: 99%